PEMBERIAN SARI KURMA TERHADAP KADARHEMOGLOBIN PADA IBU HAMIL - Sari, Anggi Yunita; Yantina, Yuli; Lathifah, Neneng Siti; Kurniasari, Devi (Universitas Malahayati Bandar Lampung, 2021)
Giving Date Palm Jiuce (Phoenix Dactylifera) To Increase of Hemoglobin levels in pregnant Background: Anemia is a biggest health problem in the world. Approximately 42% of pregnant women suffer from anemia greater than nonpregnant women. The cause of anemia in pregnant women is iron deficiency, folic acid, and acute bleeding. Dates (Phoenix dactylifera) are often referred to as foods that can increase hemoglobin levels because of their high iron content.Purposes :To determine the effect of giving palm juice to hemoglobin levels in pregnant women in the Mekar Jaya village in the working area of Mataram Merbau Health Center in South Lampung RegencGiving Date Palm Jiuce (Phoenix Dactylifera) To Increase of Hemoglobin levels in pregnant Background: Anemia is a biggest health problem in the world. Approximately 42% of pregnant women suffer from anemia greater than nonpregnant women. The cause of anemia in pregnant women is iron deficiency, folic acid, and acute bleeding. Dates (Phoenix dactylifera) are often referred to as foods that can increase hemoglobin levels because of their high iron content.Purposes : To determine the effect of giving palm juice to hemoglobin levels in pregnant women in the Mekar Jaya village in the working area of Mataram Merbau Health Center in South Lampung Regency in 2020.Method: Uses a Quasi Experimental design with a non randomized pre-test-post-test with control group approach design. The population in this study were all pregnant women with mild anemia in the village of Mekar Jaya, the working area of the Merbau Public Health Center in Mataram, South Lampung Regency. The sample size is 22 respondents, with 11 respondents included in the control group and 11 other respondents included in the experimental group.Results : Showed the average difference in increased Hb levels of pregnant women between pre-test and post-test in the experimental group was 1.5636 gr% greater than the average difference in the control group that was 0.7364 gr%. By using the t-independent statistical test the Sig. (2-tailed) 0,000 <0.05Conclusion: There is an effect of giving palm juice to the increase in hemoglobin levels in pregnant women in the village of Mekar Jaya, the working area of the Merbau Public Health Center in Mataram, South Lampung Regency in 2020. Keywords: Anemia, Hemoglobin, Palm Extract , Pregnant Woman Latar Belakang: Anemia merupakan suatu permasalahan kesehatan terbesar di dunia. Sekitar 42% ibu hamil menderita anemia lebih besar dari pada wanita tidak hamil. Penyebab anemia pada wanita hamil adalah kekurangan zat besi, asam folat, dan perdarahan akut. Sari buah kurma (Phoenix dactylifera) sering disebut sebagai makanan yang dapat meningkatkan kadar hemoglobin karena kandungan zat besi yang tinggi.Tujuan: Untuk mengetahui pengaruh pemberian sari kurma terhadap kadar Hemoglobin pada ibu hamil di desa mekar jaya wilayah kerja Puskesmas Merbau Mataram Kabupaten Lampung Selatan Tahun 2020.Metode: Menggunakan rancangan Quasi Eksperimental dengan pendekatan non randomized pre test-post test with control group design. Populasi dalam penelitian ini adalah seluruh ibu hamil dengan anemia ringan yang ada di desaMekar Jaya Wilayah Kerja Puskesmas Merbau Mataram Kabupaten Lampung Selatan. Besar sampel adalah 22 responden, dengan 11 responden masuk ke dalam kelompok kontrol dan 11 responden lainnya masuk ke dalam kelompok eksperimen.Hasil: Dari hasil penelitian menunjukkan selisih rata-rata peningkatan kadar Hb ibu hamil antara pre-test dan post-test pada kelompok eksperimen adalah 1.5636 gr% lebih besar dari pada selisih rata-rata kelompok kontrol yaitu 0.7364 gr%. Dengan menggunakan uji statistik t-independent didapatkan hasil nilai Sig. (2-tailed) 0.000 < 0.05. Kesimpulan: Ada pengaruh pemberian sari kurma terhadap peningkatan kadar hemoglobin pada ibu hamil di desa Mekar Jaya wilayah kerja Puskesmas Merbau Mataram Kabupaten Lampung Selatan Tahun 2020. Kata Kunci : Anemia, Hemoglobin, Sari Kurma, Ibu Hamily in 2020.Method: Uses a Quasi Experimental design with a non randomized pre-test-post-test with control group approach design. The population in this study were all pregnant women with mild anemia in the village of Mekar Jaya, the working area of the Merbau Public Health Center in Mataram, South Lampung Regency. The sample size is 22 respondents, with 11 respondents included in the control group and 11 other respondents included in the experimental group.Results : Showed the average difference in increased Hb levels of pregnant women between pre-test and post-test in the experimental group was 1.5636 gr% greater than the average difference in the control group that was 0.7364 gr%. By using the t-independent statistical test the Sig. (2-tailed) 0,000 <0.05Conclusion: There is an effect of giving palm juice to the increase in hemoglobin levels in pregnant women in the village of Mekar Jaya, the working area of the Merbau Public Health Center in Mataram, South Lampung Regency in 2020. Keywords: Anemia, Hemoglobin, Palm Extract , Pregnant Woman Latar Belakang: Anemia merupakan suatu permasalahan kesehatan terbesar di dunia. Sekitar 42% ibu hamil menderita anemia lebih besar dari pada wanita tidak hamil. Penyebab anemia pada wanita hamil adalah kekurangan zat besi, asam folat, dan perdarahan akut. Sari buah kurma (Phoenix dactylifera) sering disebut sebagai makanan yang dapat meningkatkan kadar hemoglobin karena kandungan zat besi yang tinggi.Tujuan: Untuk mengetahui pengaruh pemberian sari kurma terhadap kadar Hemoglobin pada ibu hamil di desa mekar jaya wilayah kerja Puskesmas Merbau Mataram Kabupaten Lampung Selatan Tahun 2020.Metode: Menggunakan rancangan Quasi Eksperimental dengan pendekatan non randomized pre test-post test with control group design. Populasi dalam penelitian ini adalah seluruh ibu hamil dengan anemia ringan yang ada di desaMekar Jaya Wilayah Kerja Puskesmas Merbau Mataram Kabupaten Lampung Selatan. Besar sampel adalah 22 responden, dengan 11 responden masuk ke dalam kelompok kontrol dan 11 responden lainnya masuk ke dalam kelompok eksperimen.Hasil: Dari hasil penelitian menunjukkan selisih rata-rata peningkatan kadar Hb ibu hamil antara pre-test dan post-test pada kelompok eksperimen adalah 1.5636 gr% lebih besar dari pada selisih rata-rata kelompok kontrol yaitu 0.7364 gr%. Dengan menggunakan uji statistik t-independent didapatkan hasil nilai Sig. (2-tailed) 0.000 < 0.05. Kesimpulan: Ada pengaruh pemberian sari kurma terhadap peningkatan kadar hemoglobin pada ibu hamil di desa Mekar Jaya wilayah kerja Puskesmas Merbau Mataram Kabupaten Lampung Selatan Tahun 2020. Kata Kunci : Anemia, Hemoglobin, Sari Kurma, Ibu Hamil